Land Acquisition for Development Interest General Based On Ecological Justice Principles: (Reflection on Constitutional Court Decision Number 137/PUU-XXI/2023) - Muchsin, Achmad; Derta Luluardi , Yunas; Khasna, Syarifa; Utami, Windi Tia (Jurusan Hukum Tata Negara Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2025)
Specifically, the basis of this research is the Constitutional Court Decision Number 137/PUU-XXI/2023 regarding the request for a judicial review that the application of Law 2/2002 is contrary to Article 28I of the 1945 Constitution of the Republic of Indonesia. This research emphasizes the importance of applying the principles of ecological justice in every decision and policy making related to the environment, especially in terms of land acquisition by the government for development in the public interest. This doctrinal legal research uses a conceptual approach, statute approach, philosophical approach for practical purposes of solving legal problems, efforts to discover law. The first target is to answer the judge's rationale in deciding case number 137/PUU-XXI/2023 related to land acquisition for development in the public interest. Second, exploring land acquisition for development in the public interest based on the principles of ecological justice. The philosophical level is expected to be able to answer the question of how land acquisition for development in the public interest can be carried out while still considering the principles of ecological justice, namely the principles of justice which according to Baxter is interpreted as justice between humans and all of nature.